Iron depletion induces hepatic secretion of biliary lipids and glutathione in rats - Prasnicka, Alena; Cermanova, Jolana; Hroch, Milos; Dolezelova, Eva; Rozkydalova, Lucie; Smutny, Tomas; Carazo, Alejandro; Chladek, Jaroslav; Lenicek, Martin; Nachtigal, Petr; Vitek, Libor; Pavek, Petr; et al. (Biochimica et biophysica acta. Molecular and cell biology of lipids, 2017)
Iron depletion (ID) has been shown to induce the liver expression of Cyp7a1, the rate-limiting enzyme initiating conversion of cholesterol to bile acids (BA), although the effect on bile acids metabolism and bile production is unknown. Therefore, we investigated changes in bile secretion and BA synthesis during diet-induced iron depletion (ID) in rats. ID increased bile flow along with augmented biliary excretion of bile acids, glutathione, cholesterol and phospholipids. Accordingly, we found transcriptional upregulation of the Cyp7a1, Cyp8b1, and Cyp27a1 BA synthetic enzymes, as well as induction of the Abcg5/8 cholesterol transporters in ID rat livers. In contrast, intravenous infusion of 3H-taurocholate failed to elicit any difference in biliary secretion of this compound in the ID rats. This corresponded with unchanged expression of canalicular rate-limiting transporters for BA as well as glutathione. We also observed that ID substantially changed the spectrum of BA in bile and decreased plasma concentrations of BA and cholesterol. Experiments with differentiated human hepatic HepaRG cells confirmed human CYP7A1 orthologue upregulation resulting from reduced iron concentrations. Results employing a luciferase reporter gene assay suggest that the transcriptional activation of the CYP7A1 promoter under ID conditions works independent of farnesoid X (FXR), pregnane X (PXR) and liver X (LXRα) receptors activation. It can be concluded that this study characterizes the molecular mechanisms of modified bile production as well as cholesterol as along with BA homeostasis during ID. We propose complex upregulation of BA synthesis, and biliary cholesterol secretion as the key factors affected by ID.
Keywords: Steroid 12-alpha-Hydroxylase; Cholesterol; Bile Acids and Salts; Humans; cholesterol; cholesterol-7-alfa-hydroxylasa; žlučové kyseliny a soli; Iron depletion; krysa rodu Rattus; Bile acid synthesis; lidé; zvířata; steroid-12-alfa-hydroxylasa; Glutathione; potkani Wistar; buněčné linie; Cholesterol 7-alpha-Hydroxylase; Cell Line; Rats, Wistar; Male; cytochrom P450 CYP271; Bile production; glutathion; Rats; Animals; Cholestanetriol 26-Monooxygenase; deficit železa; Abcg5/8; mužské pohlaví; Cyp7a1; Iron Deficiencies